DEVELOPING SCIENCE LITERACY BASED VIDEOSCRIBE LEARNING VIDEOS AT ELEMENTARY SCHOOLS - Pipit Pitriyani; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Scientific literacy is one of the skills that should be mastered in the 21st century. This scientific literacy can be implemented through learning media. The purpose of this study was to develop a learning video by using a science-based Videoscribe application. The model of development in this study was the five-step ADDIE model of refinement: analysis, design, development, implementation, and evaluation. Based on the validation from language, material, and media experts, the average percentage of the learning videos was 89.7% with the category of “very valid/very worthy.” The experimental stage of the study was carried out in three phases: one-to-one trial, small-group trial, and large-group trial. Students’ response to the science-based Videoscribe learning video in the one-to-one trial obtained a percentage of 100% in the “excellent” category. Students’ response in the small-group trial received an average of 96.25% in the “excellent” category, and students’ responses in the large-group trial received an average of 96.6% in the “excellent” category. Meanwhile, the students’ scientific literacy test results varied in each test. The one-to-one test obtained an average of 66.7% in the “good” category. The small-group test obtained an average of 58.3% in the “fairly good” category. The large-group test obtained an average of 57.3%, also in the “fairly good” category. It was concluded that the scientific literacy–based Videoscribe learning videos were suitable to be used in learning and received a very good response from students. In addition, students’ understanding of scientific literacy material was also quite good.